The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1182/blood-2006-06-030668
|View full text |Cite
|
Sign up to set email alerts
|

Nef interference with HIV-1–specific CTL antiviral activity is epitope specific

Abstract: HIV-1 Nef and HIV-1–specific cytotoxic T lymphocytes (CTLs) have important and opposing roles in the immunopathogenesis of HIV-1 infection. Nef-mediated down-modulation of HLA class I on infected cells can confer resistance to CTL clearance, but the factors determining the efficiency of this process are unknown. This study examines the impact of Nef on the antiviral activity of several CTL clones recognizing epitopes from early and late HIV-1 proteins, restricted by HLA-A, -B, and -C molecules. CTL-targeting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 49 publications
4
56
0
Order By: Relevance
“…The ability of CAR-transduced CD8 ϩ T lymphocytes to suppress the replication of HIV-1 was tested as previously described in detail (2,9,11,12,(22)(23)(24). HIV-1 strains tested were obtained from the NIH AIDS Reference and Reagent Repository, including 94US_33931N (catalog number 11250), 90_US873 (catalog number 11251), 96TH_NP1538 (catalog number 11252), and 00TZ_A246 (catalog number 11256).…”
Section: Cells and Mediamentioning
confidence: 99%
“…The ability of CAR-transduced CD8 ϩ T lymphocytes to suppress the replication of HIV-1 was tested as previously described in detail (2,9,11,12,(22)(23)(24). HIV-1 strains tested were obtained from the NIH AIDS Reference and Reagent Repository, including 94US_33931N (catalog number 11250), 90_US873 (catalog number 11251), 96TH_NP1538 (catalog number 11252), and 00TZ_A246 (catalog number 11256).…”
Section: Cells and Mediamentioning
confidence: 99%
“…HIV-infected cells expressing viral epitopes presented by HLA-C continue to be susceptible to lysis by HLA-C-restricted CTL. Prior studies using T-cell clones have shown that HLA-C-restricted CTL have equivalent cytotoxic activity relative of HLA-A-and HLA-B-restricted CTL [19,20]. There have been fewer data reported on the quantitative and qualitative characteristics of HLA-C-restricted CTL ex vivo in chronic HIV infection.…”
Section: The Phenotype Of Hla-c-restricted Ctl Is Similar To That Of mentioning
confidence: 99%
“…Direct evidence shows that HLA-C*07:02 presenting this peptide explicitly resists any downregulation of the complex by HIV-1 Nef, and cells presenting this complex retain susceptibility to a specific CTL attack (22). Additional reports demonstrated that only a limited number of mutations have been observed in this peptide [only V114I or D108E in early stage of infection and either K105R/Q or Q107R in a more elaborated study (23,42,43)] making it an excellent candidate for targeting.…”
Section: Discussionmentioning
confidence: 99%
“…293T (human embryonic kidney) cells were maintained in DMEM high-glucose medium containing 10% FCS, 100 U penicillin, and 100 mg/ml streptomycin. The peptides used in this study were Nef1 (residues 105-115 of HIV-1 Nef), KRQDILDLWVY (22); gp120 (residues 45-55 of HIV-1 Env), VYYGVPVWKEA (24); Conpep, KYFDEHYEY (25); and Nef2 (residues 90-97 of HIV-1 Nef), FLKEKGGL (26). Nef1 and gp120 were synthesized by M. Fridkin (Weizmann Institute of Science, Rehovot, Israel), Conpep by Genemed Synthesis (San Antonio, TX), and Nef2 by GL Biochem (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation